(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article is devoted to clarifying the theoretical-scientific basis of the concept of large package shares of joint-stock companies and the comparative legal analysis of national and foreign legislation. In this work, the concept of large block shares, the issues of protecting the interests of shareholders in the purchase of large block shares are discussed. Also, the importance of large block shares in society, measures to protect the rights of minority shareholders in the procurement process, the reasons for adopting a special procedure for purchasing this type of shares, and the relationship between large block shares and corporate control are studied.